The INM Way... Meeting nutrient demand of tubers - John, K. Susan; Laxminarayana, K.; Ravindran, C. S. (Indian Horticulture, 2019)
Tuber crops are highly nutrient exhaustive and an INM strategy giving emphasis to need based application of organic manures, chemical fertilizers and biofertilizers for enhancing tuber yield, improving tuber quality and maintaining soil nutrient status is highly essential under the changing global environment where tropical tuber crops like cassava can sustain and maintain its productivity and meet the calorific requirement, especially of weaker sections of global population. Crop intensification to maximize productivity for feeding the teeming population has resulted in severe nutrient mining of the soil. Under these circumstances, detailed investigation on aspects like nutrient interactions among the different components of the INM strategy for positive/synergism need to be studied to increase the input use efficiency for sustaining the productivity of these groups of crops in different agro climatic situations.